The Overturning of Roe v. Wade as a Form of Post-Colonialism - Zhafirah, Aysha Hasna (Universitas Muhammadiyah Malang, 2023)
Roe V. Wade as an important ruling and guarantor of the life of United States women who want to have an abortion, has been officially canceled in 2022. The abolition of abortion rights, which has been around for nearly 50 years, was decided by the United States Supreme Court or SCOPUS, whose members are dominated by men, even though the people discriminated against here are 51% of the United States' population, which is their female population. The inability of U.S. women, particularly minority women and those in lower-middle-class economies, to fully hold autonomy over their respective bodies without prosecution is a form of neo-colonialism that can be explained from the research methods used is the review of the Literature, especially from the perspective of Gayatri C. Spivak in literature sources, namely her book Can the Subaltern Speaks, The subalterns in this discussion are a community of mothers who need medical attention related to pregnancy and their reproductive rights. Prohibited abortions here also count life-saving procedures for some women, rulings by a group of people considered highly exclusive and discriminatory against those who need legal protection for their actions. It should be that medical accessibility can include abortion surgery, and can be guaranteed by the state as a fair and thorough application of power. The silence of women's voices in deciding this policy is a form of discrimination, not only based on gender but also race.